Analisis Kemampuan Membaca Lancar Level 2 Kelas II Sekolah Dasar - Hammi Roqiba Lubis; Chandra Chandra; Inggria Kharisma (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Fluent reading ability level 2 has an important component, namely pronouncing reading clearly with the use of pauses, intonation and appropriate expressions with the aim of getting information from the reading material being read. Fluent reading ability level 2 is very important for children to master in order to understand reading with clear pronunciation of reading, accompanied by the use of appropriate intionation, pauses and expressions. The purpose of this study was to evaluate a person's fluent reading ability level 2 in terms of reading speed with the use of appropriate pauses, intonation and expressions. Five children were assessed in a reading test involving the use of appropriate pauses, intonation and expressions. This method was chosen to understand in depth the process and factors that influence reading fluency in certain individuals. The subjects of the study were one grade 2 student totaling 5 people. Data were collected through observation, interviews with students' parents. The results showed that there were 2 children who were able to read fluently and 3 children who still had difficulty in reading fluently.